KALA DAN ASPEK DALAM BAHASA JEPANG - Bayu Aryanto (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2008)
Tense and aspect are two important variables in determining meaning of sentence in any language. Tense and aspect in Japaneseplay an important role in determining sentence meaning. The forms oftense and aspect are explicitly expressed in the lexicon and in thepredicate as well. The latter does not exist in Indonesian and it makes the uniqueness in Japanese compared to Indonesian. The uniqueness of Japanese in the study of tense and aspect must be identified and expressed in order to minimize the difficulty of Japanese language learner in understanding a proposition in Japanese.Keywords: Tense, aspect, lexicon, meaning, morphology